1968
DOI: 10.1126/science.160.3832.1119
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Changes in Lipid Bilayers: Immunological Applications

Abstract: The electrical resistance of a bimolecular lipid membrane in 0.1 molar NaCl decreases if antibody and complement are present on one side of the membrane and the homologous antigen is added to the other side. The reaction occurs within minutes and requires less than 0.1 microliter of antiserum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1969
1969
1999
1999

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…This suggests that the process of glucose permeation of the phosphatidyl choline bimolecular membrane, including that accelerated by the presence of insulin, occurs without a net flux of ions through the bilayer. These findings are compatible with those in the literature (Wood etaL, 1968;Jung, 1971)in which no change in the electrical resistance of lipid bimolecular membranes occurred during glucose permeation, and none (Hanai, Haydon &Taylor, 1965;Barfort, Arquilla & Vogelhut, 1968) when insulin was added.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that the process of glucose permeation of the phosphatidyl choline bimolecular membrane, including that accelerated by the presence of insulin, occurs without a net flux of ions through the bilayer. These findings are compatible with those in the literature (Wood etaL, 1968;Jung, 1971)in which no change in the electrical resistance of lipid bimolecular membranes occurred during glucose permeation, and none (Hanai, Haydon &Taylor, 1965;Barfort, Arquilla & Vogelhut, 1968) when insulin was added.…”
Section: Discussionsupporting
confidence: 93%
“…These observations are reminiscent of the inhibition of the excitability phenomena induced by EIM (excitability-inducing material) on BLM by protease addition to the compartment opposite to that where EIM is present (cf. Mueller & Rudin, 1969b) and the antigen-antibody reaction occurring when the components are present on opposite sides of the membrane, provided complement is supplied (Barfort, Arquilla & Vogelhust, 1968). This trypsin-sensitivity of the electrical changes induced by Ps + on anionic BLM, taken together with the expansion of stearic acid monolayers in the presence of Ps + (Shah, 1969(Shah, , 1970) and the nuclear magnetic resonance evidence of the Ps+-induced immobilization of the fatty acid chains of phosphatidylserine vesicles (Hammes & Schullery, 1970) indicates that the "polypeptide phase" extends across the lipid film and suggests that while the initial force determining the interaction is predominantly electrostatic, the overall complex formation and membrane reassembly involves important hydrophobic interactions between the lipid and polypeptide components.…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect has been reported subsequently by two other laboratories (20,42). Recently Barfort, Arquilla & Vogelhut (114) observed that if antibody and complement are on one side of a sphingomyelin-a tocopherol bilayer and the homologous antigen is added to the other side, the bilayer resistance decreases.…”
Section: Modifications Of the Electrical Properties Of Bilayers--thementioning
confidence: 99%